Does Mentoring Directly Improve Students' Research Skills? Examining the Role of Information Literacy and Competency Development - Anesito Cutillas; Eingilbert Benolirao; Johannes Camasura; Rodolfo Golbin; Kafferine Yamagishi; Lanndon Ocampo (MDPI AG, 2023)
This work proposes a structural model highlighting the research skills of undergraduate students. Due to the stages in their research project implementation, mentoring students becomes a crucial initiative in higher education institutions. Despite substantial progress in the literature linking mentoring and skills development, there is a lack of greater emphasis on research skills, especially for undergraduate students facing research work for the first time. Consequently, the direct relation between mentoring and research skills may not be straightforward. Thus, driven by social learning theory, the proposed model highlights the mediating effects of information literacy constructs and competency development on the relationship between mentoring and research skills. An empirical study of 539 participants via Partial Least Squares-Structural Equation Modeling supports six of the seven hypothesized paths. Three major theoretical contributions arise from the findings. Firstly, mentoring improves information-seeking skills and information-sharing behaviors and facilitates students' competency development due to the technical knowledge transfer from the faculty mentor to student mentees. Secondly, information literacy constructs and competency development promote research skills, emphasizing that students with those behaviors and capacities will achieve enhanced research skills. Finally, our findings suggest that mentoring does not directly translate to improved research skills; instead, information-seeking and sharing behaviors and competency development fully mediate such a link. Thus, mentors must shape these behaviors for mentoring to develop students' research skills. Theoretical and practical insights are outlined from these findings for university leadership to inform the design of mentoring initiatives for undergraduate students.